Oxidized Galectin-1 Stimulates Macrophages to Promote Axonal Regeneration in Peripheral Nerves after Axotomy - Horie, Hidenori; Kadoya, Toshihiko; Hikawa, Naoshi; Sango, Kazunori; Inoue, Hiroko; Takeshita, Kaori; Asawa, Reiko; Hiroi, Tomoko; Sato, Manami; Yoshioka, Tohru; Ishikawa, Yoshihiro (The Journal of neuroscience, 2004)
Various neurotrophic factors that promote axonal regeneration have been investigated in vivo , but the signals that prompt neurons to send out processes in peripheral nerves after axotomy are not well understood. Previously, we have shown oxidized galectin-1 (GAL-1/Ox) promotes initial axonal growth after axotomy in peripheral nerves. However, the mechanism by which GAL-1/Ox promotes axonal regeneration remains unclear and is the subject of the present study. To identify possible target cells of GAL-1/Ox, a fluorescently labeled recombinant human GAL-1/Ox (rhGAL-1/Ox) was incubated with DRG neurons, Schwann cells, and intraperitoneal macrophages from adult rats. Only the cell surfaces of intraperitoneal macrophages bound the rhGAL-1/Ox, suggesting that these cells possess a receptor for GAL-1/Ox. Experiments examining tyrosine phosphorylation revealed that rhGAL-1/Ox stimulated changes in signal transduction pathways in these macrophages. These changes caused macrophages to secrete an axonal growth-promoting factor. This was demonstrated when conditioned media of macrophages stimulated with rhGAL-1/Ox in 48 hr culture strongly enhanced axonal regeneration from transected-nerve sites of DRG explants. Furthermore, activated macrophage-conditioned media also improved Schwann cell migration from the transected-nerve sites. From these results, we propose that axonal regeneration occurs in axotomized peripheral nerves as a result of cytosolic reduced galectin-1 being released from Schwann cells and injured axons, which then becomes oxidized in the extracellular space. Oxidized galectin-1 then stimulates macrophages to secrete a factor that promotes axonal growth and Schwann cell migration, thus enhancing peripheral nerve regeneration.